Effect of the Addition Variations Cocamide Diethanolamine on Physical Characteristics Preparation of Citronella Oil Shampoo - Nyi Raden Alyaa S Eryaputri; Siti Triannisa; Alifiana F Damayanti; Muhammad Eggy Fahlevy; M Farhan; Najla Amelia; Raditha N Putri; Shilvia Fetria S; Armi Wulanawati; Alifah J Za’ani (Indonesian Journal of Chemical Science, 2023)
Dandruff is still one of the causes of reduced self-confidence which can hinder the comfort of doing activities. Dandruff is a disorder in the form of excessive flaking of dead skin on the scalp, sometimes accompanied by pruritus (itching) and inflammation. Fragrant citronella oil (Cymbopogon nardus (L.)) is a natural product and contains several chemical compounds, including citronellal, citronellol, geraniol which have antifungal and antibacterial activity, so it is used as the main ingredient in the anti-dandruff shampoo. Applying citronella oil directly to the skin is considered less practical and effective. Surfactants such as ammonium lauryl sulfate also function as cleaning agents and foaming agents as well as emulsifying agents. Cocamide DEA is used to increase the viscosity, stabilize and improve foam quality. HPMC is added to increase the thickness of the shampoo, and menthol provides a refreshing and cooling effect. The shampoo formulation was made into 3 formulations consisting of citronella oil shampoo base and various concentrations of Cocamide DEA 6%, 8%, and 10%, as well as lemon scent to offset the scent of citronella oil. The shampoo obtained is thick, has a distinctive aroma, bone white in color, pH 9 and foam height of 1-5 cm. The higher the concentration of Cocamide DEA used, the higher the foam produced in the citronella leaf extract shampoo preparation.